Balancing Privacy and Risk in the E-Messaging World. - Solomon, D. (IEEE Security and privacy : building confidence in a networked world)
Messaging within an enterprise used to be like the local water department; as long as the email flowed, no one paid any attention to it and all was good. Things are different now - messaging has become the center of a legal and regulatory maelstrom. It's the confluence of security, privacy, and opportunity within an organization. Email and instant messaging reduce the cost of delivering products, increase responsiveness to customers, enfranchise distance expertise, and evenly balance employee work/home responsibilities. Yet, these very same technologies open the door to intellectual property loss, malware intrusions, employee harassment, and compliance violations.